Das Versteck auf dem Dachboden - Lobel, Anita,Strasmann, Ilse (Atrium-Verl., 2000)
The author, known as an illustrator of children's books, describes her experiences as a Polish Jew during World War II and for years in Sweden afterwards.
Keywords: Biografie; Erlebnisbericht; Jugendbuch; Lobel; Anita <1934->; Juden; Holocaust; Jewish (1939-1945); Jewish children in the Holocaust; Jews; Rettung; Judenverfolgung; Kind; Judenvernichtung; Mädchen; Kindheitserinnerung